Assessment of Anterior Loop of Inferior Alveolar Nerve - A Cone Beam Computed Tomography Study - Juluri Sairamya Suneetha; Yalamanchili Samatha; Alaparthi Ravi Kiran; Nunsavathu Purnachandra Rao Naik; Boddu Naveen Kumar; Garikapati Anoop (Wolters Kluwer Medknow Publications, 2022)
Introduction: The anterior loop (AL) of the inferior alveolar nerve (IAN) and the mental foramen (MF) are important anatomical structures that should be taken into consideration during preoperative planning in the anterior mandibular region. This study aims to assess the prevalence, length, and type of the AL of the IAN in males and females in a South Indian population. Additionally, the distance from the MF to the lower border of the mandible is assessed. Materials and Methods: A total of 115 cone-beam computed tomography (CBCT) scans of 230 sides of mandibles were taken using a Carestream Select CS9300 CBCT machine (Carestream Dental LLC, Atlanta, USA). The scans were selected from archives and divided into three different age groups (<40, 41-60, >61 years). The scans were analyzed to detect the canal of the AL of the inferior alveolar nerve canal (IANC). The IANC, along with the AL canal and part of the incisive nerve canal, was traced using the CS 9300 software. The length of the mandibular nerve was measured for each patient in cross-sectional and panoramic views. Results: The AL was present in 92.6% of the 115 participants. Overall anterior loop length ranged between 0.9 and 15.2 mm. The mean length of AL in panoramic view on the right side was 3.284 ± 2.314 mm and it was 3.015 ± 2151 mm on the left side. Y-shaped AL was more predominant when compared to T-shaped AL in the sample. Conclusion: The prevalence of AL was relatively higher in subjects ranging from 41 to 60 years with a slight increase in female predominance.